SUBSTITUSI LIMBAH PLASTIK “HDPE” SEBAGAI PASIR TERHADAP STABILITAS DAN KELELEHAN BETON ASPAL - Qomariah Qomariah; Bobby Asukmajaya Raharjo; Sugeng Riyanto (Prokons: Jurnal Teknik Sipil, 2022)
AbstractIn fact, plastic waste after being used becomes trash and makes the environment dirty. There are many ways to make waste useful by recycling, using it for decoration and so on. Much plastic waste is applied to concrete mixtures and pavement mixtures as a substitute for sand. The use of plastic scraps as sand is applied to the pavement layer of Hotmix to increase the value of road stability, flexibility and resistance to fatiq. Plastic wastehdpe will be used on the LASTON AC-WC pavement type. Pavement for class I roads, with pavement criteria referring to the Marshall Method. Sand quality from Lumajang and gravel from Pasuruan. The design with variations of 4.5%, 5%, 5.5%, 6% plastic is replaced by 0%, 5%, 10%, 15% and 20% for sand size Ø 2.36 mm. The parameters that are reviewed are the stability and melting as well as the optimum level of asphalt, then a conclusion is drawn whether they meet the existing hypothesis. This research is continuation of 2017 research. Follow up, will be carried out further research (year 2020), with variations of plastic waste and a review of other mechanical properties in terms of the effect of addition on flexible pavement behavior.Keywords: HDPE plastics, hotmix, laston, stability, flow and KAO